2021
DOI: 10.1371/journal.pone.0249667
|View full text |Cite
|
Sign up to set email alerts
|

Initial validation of the Italian version of the Volition in Exercise Questionnaire (VEQ-I)

Abstract: The purpose of this study was to validate the Volition in Exercise Questionnaire in Italian language (VEQ-I). The translation and cultural adaptation of the VEQ-I was conducted using the forward-backward translation method. VEQ-I eighteen items correspond to the six-factors structure of the original version. The construct validity was verified by the confirmatory factor analysis (CFA) (CFI = 0.960; TLI = 0.943; RMSEA = 0.039; and SRMR = 0.040). The eighteen items were well distributed in six subscales and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Likewise, Telli et al [31] proved that the correlation between the two dimensions was statistically insignificant with a low coefficient of association. Thus, based on what was discussed, educational institutions must acknowl-edge the importance of evaluating the relationship between teachers and students [48,49] to promote and facilitate learning and encourage the child to be physically active [50].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Telli et al [31] proved that the correlation between the two dimensions was statistically insignificant with a low coefficient of association. Thus, based on what was discussed, educational institutions must acknowl-edge the importance of evaluating the relationship between teachers and students [48,49] to promote and facilitate learning and encourage the child to be physically active [50].…”
Section: Discussionmentioning
confidence: 99%
“…Motivation is an important factor in adopting and maintaining physical exercise [ 19 ]. Some studies have shown that maintaining an athlete’s motivation and well-being during the COVID-19 period of home confinement was a critical challenge [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, understanding which online modality determines greater adherence could be important for future situations. Several studies have highlighted the importance of factors such as motivation, exercise efficacy, and training frequency on adherence and participation in exercise training programs [ 19 , 20 , 21 ]. Therefore, this research aimed to analyze the differences between live streaming and a pre-recorded online modality in both coaches and gymnasts of different technical levels for: (1) adherence and frequency (times per week) of training; (2) motivation and efficacy of training; and (3) type of training performed.…”
Section: Introductionmentioning
confidence: 99%
“…Volition in Physical Exercise (18 items): Volition was measured using the Italian version of the Volition in Exercise Questionnaire [ 19 ]. It consisted of eighteen items scored on a rating scale ranging from zero ("it doesn’t match at all") to three ("exactly matches").…”
Section: Methodsmentioning
confidence: 99%
“…The VEQ-1 encompassed four volitional inhibition factors (VI) hindering an individual’s goal achievement and two volitional facilitation factors (VF) promoting goal attainment. The VI of the VEQ-1 included Reasons, Postponing Training, Unrelated Thoughts, and Approval from Others, while the VF consisted of Self-Confidence and Coping with Failure [ 19 ].…”
Section: Methodsmentioning
confidence: 99%